Three-stage hydrocarbon accumulations in the Middle Permian in the Central Sichuan Basin - Zhang, Jianyong; Liao, Yun; Lu, Pengda; Li, Wenzheng; Zhu, Kedan; Li, Zeqi; Tian, Tengzhen; Wu, Juan; Sun, Wei; Liu, Shugen; Deng, Bin (Frontiers in Earth Science, 2024)
The Middle Permain Maokou Formation is a new region of natural gas exploration in the Sichuan Basin. Currently, on the gas source, hydrocarbon accumulation process and control factors in the Sichuan Basin during the Permian are lacking. To bridge this gap, herein, we identified the filling sequence minerals inside the pores/vugs, along with the oil charge of the Maokou Formation using drill cores, thin sections, oil inclusion analysis, and U-Pb dating of calcite cements. The results showed that the reservoir space of the Maokou Formation was predominated by the residual dissolved pores/vugs, fractures, and dissolved fractures. The pores/vugs underwent four stages of mineral filling by very fine-fine (-crystalline, CC1) calcite → fine-medium calcite (CC2: from 256.4 ± 1.7 to 244.1 ± 6.3 Ma) → fibrous calcite (FC; ~183.9 ± 8.2 Ma) → coarse-macro calcite (CC3; ~171.5 ± 5.3 Ma). Combined with the homogenization temperature and salty of fluid inclusion, we considered that three stages of oil charge were present in the Maokou Formation reservoirs. The first stage involved the formation of paleo-oil reservoirs during the Late Permian to Early Triassic, corresponding to the high-maturity aqueous inclusions in CC2, with a homogenization temperature of 106.7-137.8 °C. At that time, the oil generation from the Lower Cambrian Qiongzhusi Formation rocks peaked, and the generated hydrocarbons migrated upward into the Maokou Formation through the strike-slip faults in the basin center. The second stage involved the formation of paleo-oil reservoirs during the Early Jurassic. The Permian source rocks reached the oil generation window with hydrocarbon expulsion, which was consistent with the oil inclusions in FC. The third stage involved the formation of paleo-gas reservoirs during the Middle Jurassic to Early Cretaceous, corresponding to the high-density methane inclusions and bitumen inclusions occurring in CC3, with the homogenization temperature peaking at 151.9-178 °C. The natural gas in the Middle Permian of the Central Sichuan Basin is predominantly sourced from the Lower Cambrian Qiongzhusi Formation mudstone and partially from the source rocks of the Middle Permian, indicating a significant source-reservoir conduit of the strike-slip faults in the basin center.